Assessment of the parasitic burden in smallholder pig value chains and implications for public health in Uganda - Roesel, Kristina; Dione, Michel M.; Fries, R.; Baumann, M.P.O.; Nöckler, K.; Schares, G.; Grace, Delia; Clausen, Peter-Henning (2015)
Pig production has only recently become a popular income-generating activity among smallholder farmers in Uganda; over the past 30 years, pig numbers have increased by a tenfold and pork consumption in East Africa is highest in Uganda. Pigs are not a traditional livestock species to Uganda and little is known about the occurrence of parasitic diseases that reduce growth performance and may have implications for public health. An initial systematic literature review conducted by Ocaido et al. (forthcoming), revealed huge data gaps as most zoonotic pig parasites have never been researched in East Africa. As part of comprehensive smallholder pig value chain assessments carried out by the International Livestock Research Institute (ILRI) in three administrative districts of Uganda, the presence and importance of pig parasites along the food chain was investigated. Thirty-five focus group discussions with more than 300 pig farmers showed that parasites are perceived to be a big production constraint with intestinal worms and sarcoptic mange ranking second and third after swine fever (Dione et al., 2014). Knowledge about zoonotic pig parasites is limited and practices such as free-ranging and tethering, erratic treatment and self-medication as well as lack of good hygiene on farm are common. This study presents preliminary findings on parasitic diseases that potentially compromise farm productivity (e.g. gastrointestinal helminths and sarcoptic mange) and public health (e.g. Trypanosoma spp., Trichinella spp. and Toxoplasma gondii). The research was carried out with the financial support of the Federal Ministry for Economic Cooperation and Development, Germany, and the CGIAR Research Program on Agriculture for Nutrition and Health, led by the International Food Policy Research Institute, through the Safe Food, Fair Food project at ILRI.